Study protocol for the randomised controlled trial: Ketamine augmentation of ECT to improve outcomes in depression (Ketamine-ECT study). Issue 1 (December 2015) - Trevithick, Liam; McAllister-Williams, R.; Blamire, Andrew; Branton, Tim; Clark, Ross; Downey, Darragh; Dunn, Graham; Easton, Andrew; Elliott, Rebecca; Ellwell, Clare; Hayden, Katherine; Holland, Fiona; et al.
Abstract Background There is a robust empirical evidence base supporting the acute efficacy of electroconvulsive therapy (ECT) for severe and treatment resistant depression. However, a major limitation, probably contributing to its declining use, is that ECT is associated with impairment in cognition, notably in anterograde and retrograde memory and executive function. Preclinical and preliminary human data suggests that ketamine, used either as the sole anaesthetic agent or in addition to other anaesthetics, may reduce or prevent cognitive impairment following ECT. A putative hypothesis is that ketamine, through antagonising glutamate receptors, protects from excess excitatory neurotransmitter stimulation during ECT. The primary aim of the ketamine-ECT study is to investigate whether adjunctive ketamine can attenuate the cognitive impairment caused by ECT. Its secondary aim is to examine if ketamine increases the speed of clinical improvement with ECT. Methods/Design The ketamine ECT study is a multi-site randomised, placebo-controlled, double blind trial. It was originally planned to recruit 160 moderately to severely depressed patients who had been clinically prescribed ECT. This recruitment target was subsequently revised to 100 patients due to recruitment difficulties. Patients will be randomly allocated on a 1:1 basis to receive either adjunctive ketamine or saline in addition to standard anaesthesia for ECT. The primary neuropsychological outcome measure is anterograde verbal memory (Hopkins Verbal Learning Test-Revised delayed recall task) after 4 ECT treatments. Secondary cognitive outcomes include verbal fluency, autobiographical memory, visuospatial memory and digit span. Efficacy is assessed using observer and self-report efficacy measures of depressive symptomatology. The effects of ECT and ketamine on cortical activity during cognitive tasks will be studied in a sub-sample using functional near-infrared spectroscopy (fNIRS). Discussion The ketamine-ECT study aims to establish whether or not adjunctive ketamine used together with standard anaesthesia for ECT will significantly reduce the adverse cognitive effects observed after ECT. Potential efficacy benefits of increased speed of symptom improvement and a reduction in the number of ECT treatments required will also be assessed, as will safety and tolerability of adjunctive ketamine. This study will provide important evidence as to whether adjunctive ketamine is routinely indicated for ECT given for depression in routine NHS clinical practice. Trial Registration Current Controlled Trials:ISRCTN14689382 (assigned 30/07/2012); EudraCT Number: 2011-005476-41